Chronic Developmental Lead Exposure Reduces Neurogenesis in Adult Rat Hippocampus but Does Not Impair Spatial Learning - Gilbert, M. E.; Kelly, M. E.; Samsam, T. E.; Goodman, J. H. (Toxicological sciences, 2005)
The dentate granule cell (DG) layer of the hippocampal formation has the distinctive property of ongoing neurogenesis that continues throughout adult life. Although the function of these newly generated neurons and the mechanisms that control their birth are unknown, age, activity, diet and psychosocial stress have all been demonstrated to regulate this type of neurogenesis. Little information on the impact of environmental insults on this process has appeared to date. Developmental lead (Pb) exposure has been well documented to impair cognitive function in children and animals and reduce activity-dependent synaptic plasticity in the hippocampus of rodents. Therefore, we examined the effects of this classic environmental neurotoxicant on hippocampal-dependent learning and adult neurogenesis in the hippocampus. Pregnant rats were exposed to a low level of Pb-acetate (0.2%) via the drinking water from late gestation (GD 16) until weaning on postnatal day 21 (PN 21). At weaning, half of the Pb-exposed animals were weaned to control drinking water and the remainder were maintained on Pb water until termination of the study. Animals were paired- housed and on PN 75 were administered a series of injections of a thymidine analog bromodeoxyuridine (BrdU), a marker of DNA synthesis that labels proliferating cells and their progeny. At 12-h intervals for 12 days, rats received an ip injection of BrdU (50 mg/kg). Subjects were sacrificed and perfused 24 h and 28 days after the last injection. Spatial learning was assessed in an independent group of animals beginning on PN 110 using a Morris water maze. No Pb-induced impairments were evident in water maze learning. Immunohistochemistry for the detection of BrdU-labeled cells was performed on 40-μm coronal sections throughout the hippocampus. Continuous exposure to Pb (Life) reduced the total number of BrdU-positive cells at 28 days without affecting the total number of labeled cells evident 24 h after the last injection. No differences in the number of progenitor cells labeled or surviving were seen between control and treated animals whose Pb exposure was terminated at weaning. Double labeling with BrdU and the glial specific marker, glial acidic fibrillary protein (GFAP) indicated that the bulk of the surviving cells were of a neuronal rather than a glial phenotype. These data reveal that chronic low-level Pb exposure reduces the capacity for neurogenesis in the adult hippocampus. Despite deficits in synaptic plasticity previously reported from our laboratory (e.g., Gilbert, M. E., Mack, C. M., and Lusley, S. M. Brain Res. 1996; 736, 118–124), and now structural plasticity, no significant impact on spatial learning was detected.